Could Serum TSH Levels Predict Malignancy in Euthyroid Patients Affected by Thyroid Nodules with Indeterminate Cytology? - Carlo Cappelli; Ilenia Pirola; Elena Gandossi; Mario Rotondi; Davide Lombardi; Claudio Casella; Fiorella Marini; Maura Saullo; Barbara Agosti; Elena Di Lodovico; Luca Chiovato; Alberto Ferlin; et al. (International Journal of Endocrinology)
Background. Serum TSH levels in the upper-normal range were reported to be associated with increased risk of thyroid malignancy. However, measurement of TSH levels is currently not recommended for assessing the risk of malignancy in patients with newly diagnosed thyroid nodules. Objective. To evaluate a possible relationship between the serum levels of TSH and the histological outcome of patients undergoing thyroidectomy for thyroid nodules with indeterminate cytology. Materials and Methods. We collected the clinical data of all patients who had performed ultrasound-guided FNA of thyroid nodules with cytological diagnosis of indeterminate lesions (TIR3A and TIR3B) and serum TSH levels within the normal range. All patients had been submitted to thyroid surgery (hemi or thyroidectomy, as appropriate), and histological diagnosis had been performed. Results. A histological diagnosis of thyroid malignancy was rendered in 74/378 (19.6%) nodules. Patients with histologically proven thyroid malignancy were characterized by higher serum levels of TSH as compared to patients with histologically proven benign nodules (3.03 ± 1.16 vs. 2.37 ± 1.19 mIU/L, p<0.001). To further analyze the role of serum TSH in predicting thyroid cancer, patients were stratified in 4 groups according to quartiles of TSH concentrations. The prevalence of malignancy was 12.2% for the first quartile and 50.0% for the last quartile. ROC curve analysis identified that a serum TSH level of ≥2.7 mIU/L predicted thyroid malignancy with a sensitivity of 61% and a specificity of 65%. Conclusions. TSH levels in the upper-normal range are associated with an increased risk of thyroid malignancy in patients affected by thyroid nodules with indeterminate cytology at FNA. The measurement of serum TSH levels represents an easily performed additional tool for decision-making in patients with indeterminate cytological findings.